2018
DOI: 10.12659/ajcr.907304
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exertional Compartment Syndrome with Rhabdomyolysis: Case Report and Review of Literature

Abstract: Patient: Male, 17Final Diagnosis: Acute exertional compartment syndromeSymptoms: Foot drop • leg pain • paresthesiaMedication: —Clinical Procedure: FasciotomySpecialty: Orthopedics and TraumatologyObjective:Rare diseaseBackground:Acute exertional compartment syndrome (AECS) is a rare cause of leg pain often associated with a delay in diagnosis and potentially leading to irreversible muscle and nerve damage.Case Report:We present the case of a previously healthy, high-level athlete who presented with the acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Of the 126 studies found through the search strategy, 10 met the proposed inclusion criteria and were in compliance with the CARE recommendations.Of the 10 articles selected to compose the present review, two reported cases of soccer athletes, 23,25 three of football, 17,19,21 two of swimming, 22,24 one of wrestling, 20 one of 24-hour cross-country skiing, 18 and one of mixed martial arts (MMA). 26 Of the six modalities described in the studies, four presented characteristics of physical contact sports (soccer, football, wrestling, and MMA) and two were related to individuals sports (skiing and swimming).The age range of the athletes varied between 16 to 41 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 126 studies found through the search strategy, 10 met the proposed inclusion criteria and were in compliance with the CARE recommendations.Of the 10 articles selected to compose the present review, two reported cases of soccer athletes, 23,25 three of football, 17,19,21 two of swimming, 22,24 one of wrestling, 20 one of 24-hour cross-country skiing, 18 and one of mixed martial arts (MMA). 26 Of the six modalities described in the studies, four presented characteristics of physical contact sports (soccer, football, wrestling, and MMA) and two were related to individuals sports (skiing and swimming).The age range of the athletes varied between 16 to 41 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Acute exertional compartment syndrome with rhabdomyolysis: case report and review of literature - McKinney et al., 2018. 17…”
Section: Methodsmentioning
confidence: 99%
“…However, in Livingston's series, despite the high average intracompartmental pressures measured (91 mm Hg), there was no correlation between pressure and muscle damage, but a strong correlation of a time to diagnose more than 24 hours and myonecrosis is evident. This year, McKinney et al reported a case of AECS affecting the anterior tibial compartment presenting with foot drop which was successfully treated with anterior lateral fasciotomies and rhabdomyolysis-supportive treatment, giving him full recovery apart from inability to extend of his hallux due to EHL necrosis [6]. Nicholson et al reported AECS of the peroneal compartment on a 24-year-old healthy female after prolonged horse riding [7].…”
Section: Unusual Conditionsmentioning
confidence: 99%
“…12 Acute compartment syndrome (ACS) can result from direct impact injuries to soft tissue structures, ischemia related to vascular injury, extremity fractures, or more rarely, overexertion. 12,15,24 Acute exertional compartment syndrome (AECS) is a rare subset of ACS, characterized by an increase in intracompartmental pressure without a specific traumatic event. 15,24 The lower leg is composed of 4 compartments: anterior, lateral, superficial posterior, and deep posterior.…”
mentioning
confidence: 99%
“…12,15,24 Acute exertional compartment syndrome (AECS) is a rare subset of ACS, characterized by an increase in intracompartmental pressure without a specific traumatic event. 15,24 The lower leg is composed of 4 compartments: anterior, lateral, superficial posterior, and deep posterior. 8 Pain with passive stretch of the muscles within the affected compartment(s) is a hallmark of early clinical diagnosis prior to the onset of sensory or motor changes.…”
mentioning
confidence: 99%